Competitive influences of running applications on training habits - Shei, R.-J. (The Physician and Sportsmedicine, 2018)
The use of running applications (RAs) has recently been shown to neither increase nor decrease the risk of running-related injuries (RRIs). However, it is important to note that the study reporting these findings did not account for the influence of virtual competition or challenges, such as virtual leaderboards for certain popular "segments" and monthly "challenges" which reward users for completing predefined tasks in a given time period. Both of these factors may affect the training behaviors of RA users, and indeed may contribute to the risk of RRIs. In particular, the latter may mimic a predefined running scheme, which had a positive relationship with RRIs. Therefore, it is important for future studies to elucidate whether virtual competitions or challenges promoted by RAs influence running behavior, and consequently, the risk for RRIs.